Hemodynamic variables in piglets anesthetized with isoflurane or propofol, kept under spontaneous ventilation and FIO2 of 0.5 - Ido, C. K. [UNESP]; Silva, P. E.S.; Silva, H. R.A. [UNESP]; Biteli, E. G.F.; Carneiro, R. L.; Lopes, P. C.F.; Gering, A. P.; Nunes, N. [UNESP] (FapUNIFESP (SciELO), 2019)
This study aimed to evaluate comparatively the effects of propofol or isoflurane on hemodynamic variables in piglets that received inspired oxygen fraction (FIO2) of 0.5 under spontaneous ventilation. Therefore, sixteen piglets weighing 16±1.1kg, were randomly divided into two groups: GI (Isoflurane and FIO2 of 0.5) and GP (Propofol and FIO2 of 0.5). Heart rate (HR), systolic, diastolic and mean arterial pressure (SAP, DAP and MAP), central venous pressure (CVP), cardiac output (CO), mean pulmonary arterial pressure (mPAP) and mean capillary pulmonary pressure (mCPP) were assessed 40 minutes after anesthetic induction (T0), followed by 15 minutes intervals (from T15 to T60). The variables cardiac index (CI), stroke volume (SV), stroke index (SI), total peripheral resistance (TPR), total peripheral resistance index (TPRI), pulmonary vascular resistance (PVR), and pulmonary vascular resistance index (PVRI) were calculated. SAP and TPRI were significantly different between groups at T30 and T60 (P< 0.05) with higher GP values being recorded. There were no differences in the other variables, however, GP presented mean closer to normality on most of the analyzed variables. Therefore, we conclude that total intravenous anesthesia with propofol presented greater stability of the hemodynamic variables evaluated.
Keywords: Cardiovascular; Inhalation; Intravenous; Oxygen; Pigs